1988
DOI: 10.1128/aem.54.12.3156-3161.1988
|View full text |Cite
|
Sign up to set email alerts
|

Production and Further Characterization of an Alkaline Elastase Produced by Alkalophilic Bacillus Strain Ya-B

Abstract: The characteristics of the obligate alkalophilic Bacillus sp. strain Ya-B, which produces alkaline elastase extracellularly, were examined. This strain grew at pH 7.0 only in the presence of 1% or more NaCl. Its fatty acid distribution pattern was similar to that of other Bacillus species in which iso-C15 and anteiso-Cl5 were the most abundant fatty acids. About 120 mg of enzyme was recovered from 1 liter of culture broth in a medium (pH 10.1) containing mainly glucose, soymeal, and glycerol. The antiserum aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…A number of possibilities might explain these earlier results. Elastases, which are found in many organisms, including mammals (4,16,22,38,46), bacteria (19,25,50,51), schistosomes (23, 24), and fungi (18,27,34), may be conserved structurally and thus be essentially weak immunogens (52). If the native fungal elastase is structurally similar to murine elastase, then it may not be sufficiently foreign to induce a vigorous immune response.…”
Section: Discussionmentioning
confidence: 99%
“…A number of possibilities might explain these earlier results. Elastases, which are found in many organisms, including mammals (4,16,22,38,46), bacteria (19,25,50,51), schistosomes (23, 24), and fungi (18,27,34), may be conserved structurally and thus be essentially weak immunogens (52). If the native fungal elastase is structurally similar to murine elastase, then it may not be sufficiently foreign to induce a vigorous immune response.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of B. subtilis ATCC strain 14416 [85] and B. sphaericusstrain BSE 18 [86], enzyme production was growth-associated and it occurs at the mid-exponential phase, and often a rapid auto deactivation process was observed after the culture reached the maximum enzyme activity. During alkaline protease production, it was also observed that the pH of the fermented medium dropped from alkaline to acidic; for instance, from pH 10.1 to 8.5 in the case of an alkalophilic Bacillus strain Ya-B [87].…”
Section: Organism Referencesmentioning
confidence: 99%
“…The low activity of elastase produced by microorganisms has greatly hampered the research on the role of microbial elastases, and only a few attempts have been made to increase elastase productivity by manipulating physiological conditions and medium compositions (Tsai et al, 1988;Chen et al, 2002). Some recent studies in the field of the optimization of fermentation conditions have reported a significant increase in the yields of elastase (Chen et al, 2002;He et al, 2004).…”
Section: Runsmentioning
confidence: 99%
“…In recent years, some researchers have found that although many Gram-negative and -positive bacteria secrete elastase, the bacterial forms of elastase either have a low activity or harmful effects so that few of them are of medical or industrial values (Tsuzuki and Oka, 1965;Ozaki and Shiio, 1975;Clark et al, 2000;Janda and Abbott, 1999). Others have exerted their efforts in isolating and screening microorganisms that produce a high level of elastase (Shibata et al, 1993;Tsai et al, 1988;Zins et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation